Effects of Infill Wall Ratio on the Period of Reinforced Concrete Framed Buildings - Kocak, Ali; Yildirim, M. Kasim (MULTI-SCIENCE PUBL CO LTD, 2011)
Realistic estimates of the earthquake induced natural period of reinforced concrete buildings lead to enhanced reliability in design. Several national building codes and researchers have suggested various empirical formulas and approximations to predict the fundamental natural period of buildings with or without infill walls. In this paper, the effect of infill walls on the natural vibration period of framed reinforced concrete buildings is investigated. Reinforced concrete framed buildings of various storey heights and different infill wall ratios are modeled to examine the effect of the infill walls on the general behavior of the structures. Linear solutions for the structures are performed and their basic vibration periods are determined. As a result of there analyses, a new relationship for the changes in the building periods according to the infill wall ratio is developed for reinforced concrete framed buildings. The predictions of the proposed relation and other correlations found in the codes of various countries are compared.
Keywords: infill wall; vibration period; reinforced concrete framed buildings; fundamental period; earthquake; RC FRAMES; MASONRY; FORMULAS; DAMAGE; Construction & Building Technology; Engineering